Wild cereal grain consumption among Early Holocene foragers of the Balkans predates the arrival of agriculture - Cristiani, Emanuela; Radini, Anita; Zupancich, Andrea; Gismondi, Angelo; D'Agostino, Alessia; Ottoni, Claudio; Carra, Marialetizia; Vukojičić, Snežana; Constantinescu, Mihai; Antonović, Dragana; Price, T Douglas; Borić, Dušan (eLife, 2021)
Forager focus on wild cereal plants has been documented in the core zone of domestication in southwestern Asia, while evidence for forager use of wild grass grains remains sporadic elsewhere. In this paper, we present starch grain and phytolith analyses of dental calculus from 60 Mesolithic and Early Neolithic individuals from five sites in the Danube Gorges of the central Balkans. This zone was inhabited by likely complex Holocene foragers for several millennia before the appearance of the first farmers ~6200 cal BC. We also analyzed forager ground stone tools (GSTs) for evidence of plant processing. Our results based on the study of dental calculus show that certain species of Poaceae (species of the genus Aegilops) were used since the Early Mesolithic, while GSTs exhibit traces of a developed grass grain processing technology. The adoption of domesticated plants in this region after ~6500 cal BC might have been eased by the existing familiarity with wild cereals.
Keywords: dental calculus; Mesolithic foragers; plant foods; stone tools